MOTIF TANAMAN KOPI PADA BAJU TALUAK BALANGO - Indah Erda Ningsih; Dini Yanuarmi; Rahmad Washinton; Mirda Aryadi; Fadri Rahmat (Style : Journal of Fashion Design, 2022)
The coffee plant has a taproot, straight down, short and strong. The taproot is approximately 45-50 cm long, which basically has 4-8 side roots that descend down 23 cm. Coffee leaves are long, striped to the sides, wavy, dark green, and tapered at the ends. Leaves grow and are arranged side by side in the armpits of the stems, branches and twigs. A pair of leaves located in the same plane and branches that grow horizontally.The shape of the coffee plant that has been described, the creators make it as a source of ideas as an ornamental motif. The coffee plants that are used as motifs are the flower parts, leaves, fruit, and twigs that are applied to the balango taluak. Taluak balango is clothing for men in Minangkabau, the hallmark of the taluak balango shirt is using seams on the side of the shirt where there is a siba with a length below the waist, a round neck without a collar and slightly slit to the chest. The balango taluak shirt is usually worn with a trouser suit, worn in events, traditional ceremonies, religious and other formal events. The method used in the creation of this work is the method of exploration, design and embodiment with an aesthetic approach. This work is expected to be able to contribute to the wider community, by introducing the depiction of coffee plant motifs on balango taluak. The balango taluak used and used in the Minangkabau area does not have specific provisions related to its decorative motifs.